The 6 degrees-of-freedom range of motion of the L1–S1 vertebrae in young and middle-aged asymptomatic people - Xu, Fei; Zhou, Siyu; Li, Zhuofu; Jiang, Shuai; Chen, Ze; Sun, Zhuoran; Li, Weishi (Frontiers in Surgery, 2022)
Study design Controlled laboratory study. Objective To determine the 6 degrees-of-freedom (DOF) of lumbar vertebra in vivo during different functional activities in young and middle-aged asymptomatic subjects Methods 26 asymptomatic subjects (M/F, 15/11; age, 20–55 years) were recruited. They were divided into two groups, young group (number: 14; age: 20-30 years old) and middle-aged group (number: 12; age: 45-55 years old). The lumbar segment of each subject was scanned by computed tomography (CT) for construction of three-dimensional (3D) models of the vertebra from L1 to S1. The lumbar spine was imaged by a dual fluoroscopic system when the subject performed different trunk postures. The 3D models of vertebrae were matched to two fluoroscopic images simultaneously in software. The ROM of vertebrae in young and middle-aged group were compared by multiway analysis of variance respectively. Results During the supine to the upright posture, vertebral rotation of the L1-S1 occurred mainly around the mediolateral axis (mean: 3.9±2.9°). Along the mediolateral axis vertebral translation was significantly lower at L1-2 (7.7±2.4mm) and L2-3 (8.0 ±3.5mm) than those at L3-4 (1.6 ±1.2mm), L4-5 (3.3 ±2.6mm) and L5-S1 (2.6±1.9mm). At the L4–5 level, young group had higher rotational ROM than that in middle-aged group around all three axes during left-right bending. Along the anteroposterior axis, young group had lower translational ROM at L4-5 than that in the middle-aged group during left-right bending (4.6±3.3mm vs 7.6±4.8mm; P<0.05). At L5-S1, young group had lower translational ROM than that in the middle-aged group during flexion-extension, left-right bending and left-right torsion. Conclusion This study explored the lumbar vertebral ROM at L1-S1 during different functional posture in both young and middle-aged volunteers. There were higher coupled translations at L3-4 and L4-5 than upper lumbar segments during supine to upright. The vertebral rotation decreased with age. Besides, the older subjects had higher anteroposterior translation at L4–5 segment and higher mediolateral translation at L5–S1 segment than those in the young group. These data might provide basic data to be compared with spinal pathology.